Akumulasi Logam Berat pada Tanaman Pepaya (Carica papaya) Akibat Penggunaan Air Limbah Rumah Sakit sebagai Media Tumbuh - Suhendrayatna Suhendrayatna; Elviani Elviani; Elvitriana Elvitriana (Jurnal Serambi Engineering, 2022)
Wastewater from the outlet of hospital's Wastewater Treatment Plant (WWTP) is expected to be used for watering plants as an effort to water use efficiently. To answer this assumption, this research was carried out to examine the effects of hospital wastewater as a plant growth medium on the accumulation of pollutants in papaya (Carica papaya) leaves and fruit. Local papaya seeds were grown on the land around the hospital's WWTP and the plants were watered every day with wastewater. Plants were well cared for without adding other additives as fertilizer and their growth was observed. After 8 months of treatment, the fruits and leaves of plants were harvested and destructed using HNO3 and H2SO4 to measure the heavy metal content using the Atomic Absorption Spectrophotometer, Shimadzu A630. Results showed that when wastewater was used as a growth medium, metals Hg, Cd, and Pb were found to accumulate in papaya fruit with a concentration of 0.179; 0.582; and 2,327 mg/kg, while other metals such as Cr and As were not found to accumulate in papaya fruit. Metal accumulation was also found in papaya leaves with Hg content of 0.739 mg/kg and Cd of 0.582 mg/kg, while others metals Cr, Pb, and As were not found in the papaya leaves. These results indicate that the main source of heavy metal accumulation in papaya plants came from wastewater from the WWTP outlet containing heavy metals.